Alumina Surface Treated Pigmentary Titanium Dioxide with Suppressed Photoactivity (Journal of Coating Science and Technology, 2014)
The aim of the optimization of the technological process was to coat the surface of the pigment in a controlled manner and to supress photoactivity in the titanium dioxide (TiO2) pigment. As part of this research, a systematic approach to TiO2 pigment surface treatment with alumina was conducted. Surface treatment with alumina plays a significant role in the improvement of TiO2 properties (e.g. weather resistance and photostability). This research encompasses a raw material analysis and process conditions study. Sodium aluminate and aluminium sulphate were used as a source of alumina hydroxide. The effectiveness of surface treatment was determined using scanning-transmission (STEM) and transmission (TEM) electron microscopy. The photoactivity of pigmentary TiO2 was determined before and after surface treatment. A controlled surface treatment process resulted in pigmentary TiO2 particles with uniform amorphous layers, which supressed the photoactivity of the pigment.